2019
DOI: 10.3390/fermentation5040098
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Microbial Consortium for Enhanced Metabolite Production from Simulated Food Waste

Abstract: Food waste disposal and transportation of commodity chemicals to the point-of-need are substantial challenges in military environments. Here, we propose addressing these challenges via the design of a microbial consortium for the fermentation of food waste to hydrogen. First, we simulated the exchange metabolic fluxes of monocultures and pairwise co-cultures using genome-scale metabolic models on a food waste proxy. We identified that one of the top hydrogen producing co-cultures comprised Clostridium beijerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…The stimulating effect of cross-feeding of lactate on hydrogen synthesis was also observed in co-cultures of two bacterial strains: the butyrate- and hydrogen-producing Clostridium beijerinckii and the lactate-producer Yokenella regensburgei ( Schwalm et al, 2019 ) or the hydrogen- and lactate-producing Bacillus cereus and the hydrogen- and butyrate-producing Brevundimonas naejangsanensis ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 81%
“…The stimulating effect of cross-feeding of lactate on hydrogen synthesis was also observed in co-cultures of two bacterial strains: the butyrate- and hydrogen-producing Clostridium beijerinckii and the lactate-producer Yokenella regensburgei ( Schwalm et al, 2019 ) or the hydrogen- and lactate-producing Bacillus cereus and the hydrogen- and butyrate-producing Brevundimonas naejangsanensis ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 81%
“…Studies on thermophilic DF of sugarcane vinasse also showed lactate as the primary substrate for biohydrogen production and the relevance of pH in this process [24,25]. Cross-feeding of lactate was also observed in reduced MCs composed of two components: butyrate-producing Clostridium beijerinckii and lactateproducer Yokenella regensburgei [26] or butyrateproducing Clostridium butyricum and lactate-producer Sporolactobacillus vineae [27]. Furthermore, pure cultures of Clostridium acetobutylicum [28], Butyribacterium methylotrophicum [29], Clostridium diolis [30], Clostridium butyricum [18] and Clostridium tyrobutyricum [31,32] anaerobically grown in media with acetate and lactate as exclusive carbon sources produced carbon dioxide, hydrogen and butyrate.…”
Section: Introductionmentioning
confidence: 92%
“…Studies on thermophilic dark fermentation of sugarcane vinasse also showed lactate as the primary substrate for biohydrogen production and relevance of pH in this process [24,25]. Cross-feeding of lactate was also observed in reduced microbial communities composed of two components: butyrateproducing Clostridium beijerinckii and lactate-producer Yokenella regensburgei [26]. Furthermore, pure cultures of Clostridium acetobutylicum [27], Butyribacterium methylotrophicum [28], Clostridium diolis [29], Clostridium buttyricum [18] and Clostridium tyrobutyricum [30,31] anaerobically grown in media with acetate and lactate as exclusive carbon sources produced carbon dioxide, hydrogen and butyrate.…”
Section: Introductionmentioning
confidence: 93%